Effect of selective laser melting parameters of microstructure of Inconel 738LC superalloy - Tan, Daryl Si Han (Nanyang Technological University, 2023)
Selective Laser Melting (SLM) is a popular additive manufacturing process which enables the efficient fabrication of complex geometries from a wide range of materials. Inconel 738LC (Low Carbon) is a nickel-based superalloy commonly used in high temperature and high-performance applications due to its exceptional mechanical properties in extreme environments. However, the processing of this alloy using SLM poses a significant challenge due to the propensity to work harden and develop cracks. This study investigated the effect of process parameters on the microstructure, hardness and cracking susceptibility of Inconel 738LC processed by SLM. The investigation was performed by analysis of micrographs that were mainly obtained from optical microscopy techniques. Scanning electron microscopy was also briefly used to observe the internal structure of cracks. The findings revealed that increasing laser power and decreasing scanning speed leads to a larger dendrite arm spacing, indicating a lower cooling rate and reduced surface roughness. Additionally, an increase in scanning speed and laser power both lead to an increase in the width of the melt pool. However, an increase in laser power and scanning speed results in a deeper and shallower depth respectively. The crack analysis indicates that an increase in laser power results in an increase in surface crack density, while the opposite can be seen when there is an increase in scanning speed. A similar pattern was also observed regarding the average crack length observed on the SLM-fabricated samples used for this study. Finally, micro hardness testing shows an increase in hardness value with an increase in scanning speed and laser power.